The potential for micro-takaful in Sudan: understanding public perception and adoption challenges - Abubaker, Reem Abbas; Zakariyah, Habeebullah; Al-Shaghdari, Fahd Mohammed Obad (IIUM Press, 2025)
This study explores the perceptions and barriers to Micro-Takaful adoption among Sudanese citizens, based on a quantitative survey of 428 respondents. Understanding public perceptions is essential for promoting health Micro-Takaful as a practical alternative for financial protection among low-income individuals in Sudan. Despite health Micro-Takaful’s potential to provide financial protection to low-income populations, its adoption in Sudan remains limited. Data was collected through an online questionnaire targeting Sudanese adults aged 18 and above and then the analysis was conducted using SPSS version25. The survey findings highlight that health Takaful coverage increases with age, likely due to greater health awareness or employment benefits, but significant gaps remain, especially among younger and middle-aged adults. This highlights the need for targeted strategies to improve Takaful uptake across all age groups, and targeted interventions to increase health Takaful access in less covered areas, which affect the acceptance of Micro-Takaful products. This paper presents a detailed analysis of Sudanese perception towards Takaful and Micro-Takaful adoption in Sudan